(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
At the end of 2016 and the beginning of 2017, a period of new reforms began in Uzbekistan. Uzbekistan has set itself the goal of creating a state with a strong economy. In order to achieve this goal, he aimed to reduce the state property and its share in the economy and give a wide place to private ownership. For this purpose, on February 7, 2017, the presidential decree "On the "Strategy of actions" for the further development of the Republic of Uzbekistan" was adopted. In paragraph 3 of this decree entitled "Further development and liberalization of the economy" in Uzbekistan in 2017-2021, based on the principle "If the people are rich, the state will be rich and strong", reducing the state’s participation in the economy, further expanding the privatization of state property and simplifying its procedures, economic the task of reducing state participation in the charter funds of operating entities, creating favorable conditions for the development of private entrepreneurship on the basis of state-owned privatized objects was determined.